Interactive effects of vitamin D and serum uric acid concentration on protein-energy wasting in maintenance hemodialysis patients: Vitamin D and serum uric acid effects on PEW in MHD - Huang, Wenbin; Luo, Luping (Cellular and Molecular Biology, 2023)
This study aimed to explore the influence of the interaction between vitamin D level and blood uric acid level on protein-energy wasting (PEW) in patients with Maintenance hemodialysis (MHD), in order to provide a solution for disease prevention. For this aim, a total of 150 patients with maintenance hemodialysis aged 30-79 years in a hospital were included in the study. The logistic regression model was used to analyze the relationship between vitamin D level, blood uric acid level and PEW, and the additive interaction was evaluated by calculating the relative excess risk ratio (RERI) attributive ratio (AP) and synergy index (S) of the interaction. Finally, the ROC curve was drawn to evaluate the diagnostic value of vitamin D level and blood uric acid level for PEW. In this study, the detection rate of PEW was 68%, low vitamin D level was 57.33%, and high blood uric acid level was 64.67%. Compared with non-low vitamin D levels, the PEW risk was OR=16.794, 95%CI: 4.973-60.356; Compared with those without high uric acid levels, the PEW risk was OR=7.599, 95%CI: 2.460-23.468. However, there was no multiplicative interaction between the two on PEW risk (OR=0.345, 95%CI: 0.060-1.983, P=0.233). In the additive interaction analysis, the PEW risk OR=43.992,95%CI: 12.795-151.253, higher than those with only high uric acid levels or only low vitamin D levels, the combination of the two had a summative interaction with PEW risk, with a RERI of 20.599 (95%CI: -26.158-67.356) API was 0.468 (-0.159-1.095) and S was 1.920 (0.569-6.483). In conclusion, both vitamin D deficiency and high uric acid levels were associated with an increased risk of PEW in MHD patients, and low vitamin D and high uric acid levels had a summative interaction with protein-energy expenditure risk.